2019
DOI: 10.1017/jfm.2019.413
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent flow of finite-size spherical particles in channels with viscous hyper-elastic walls

Abstract: We study single-phase and particulate turbulent channel flows, bounded by two incompressible hyper-elastic walls at bulk Reynolds number 5600. Different wall elasticities are considered with and without a 10% volume fraction of finite-size neutrally-buoyant rigid spherical particles. A fully Eulerian formulation is employed to account for the fluid-structure interaction at the elastic walls interfaces together with a direct-forcing immersed boundary method (IBM) to model the coupling between the fluid and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…spherical and isotropic particles (Lucci, Ferrante & Elghobashi 2010; Gualtieri et al. 2013; Capecelatro, Desjardins & Fox 2018; Ardekani & Brandt 2019; Ardekani, Rosti & Brandt 2019; Sozza et al. 2020), anisotropic particles and fibres (Andersson, Zhao & Barri 2012; Ardekani et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…spherical and isotropic particles (Lucci, Ferrante & Elghobashi 2010; Gualtieri et al. 2013; Capecelatro, Desjardins & Fox 2018; Ardekani & Brandt 2019; Ardekani, Rosti & Brandt 2019; Sozza et al. 2020), anisotropic particles and fibres (Andersson, Zhao & Barri 2012; Ardekani et al.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of turbulence in non-dilute conditions has been the subject of studies regarding several classes of particulate and multiphase flows, e.g. spherical and isotropic particles (Lucci, Ferrante & Elghobashi 2010;Gualtieri et al 2013;Capecelatro, Desjardins & Fox 2018;Ardekani, Rosti & Brandt 2019;Sozza et al 2020), anisotropic particles and fibres (Andersson, Zhao & Barri 2012;Ardekani et al 2017a;Olivieri et al 2020bOlivieri et al , 2021, as well as droplets or bubbles (Dodd & Ferrante 2016;Freund & Ferrante 2019;Rosti et al 2019;Cannon et al 2021). Overall, when the concentration is large enough, this modulation effect typically causes a substantial departure from the classical phenomenology observed for a purely Newtonian fluid (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the thickness of the particle-wall layer, they proposed a relation able to predict the friction Reynolds number as a function of the bulk Reynolds number (Costa et al 2016(Costa et al , 2018. Ardekani, Rosti & Brandt (2019) showed in a numerical experiment that removing the particle-wall layer results in turbulence attenuation with respect to single-phase flow, while the presence of this layer contributes to larger velocity fluctuations close to the wall for lower particle volume fractions.…”
Section: Wall-bounded Turbulent Flowsmentioning
confidence: 99%
“…2016, 2018). Ardekani, Rosti & Brandt (2019) showed in a numerical experiment that removing the particle–wall layer results in turbulence attenuation with respect to single-phase flow, while the presence of this layer contributes to larger velocity fluctuations close to the wall for lower particle volume fractions.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting turbulence modulation effects have been the subject of previous studies over different classes of multiphase turbulent flows, i.e. considering isotropic (Lucci, Ferrante & Elghobashi 2010;Gualtieri et al 2013;Uhlmann & Chouippe 2017;Capecelatro, Desjardins & Fox 2018;Ardekani, Rosti & Brandt 2019;Yousefi, Ardekani & Brandt 2020) or anisotropic (Andersson, Zhao & Barri 2012;Olivieri et al 2020b,a;Wang et al 2022) solid particles, as well as droplets or bubbles (Dodd & Ferrante 2016;Freund & Ferrante 2019;Rosti et al 2019;Cannon et al 2021), typically focusing on the alteration of both the bulk flow properties as well as the scale-by-scale energy distribution. In particular, Lucci et al (2010) and Yousefi et al (2020) showed that Taylor-length-scale-sized spheres reduce turbulent kinetic energy at the large scales and enhance its energy content at the small scales.…”
Section: Introductionmentioning
confidence: 99%